White Paper: Radiology Curriculum for Undergraduate Medical Education in Germany and Integration into the NKLM 2.0. - Dettmer, Sabine; Barkhausen, Joerg; Volmer, Erik; Mentzel, Hans-Joachim; Reinartz, Sebastian; Voigt, Florian; Wacker, Frank K.; Baessler, Bettina; Adam, G.; Antoch, G.; Attenberger, Ulrike; Bamberg, F.; et al. (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
OBJECTIVE: The aim was to develop a new curriculum for radiology in medical studies, to reach a national consensus and to integrate it into the new national competence-based learning objectives catalog (NKLM 2.0). In this statement of the German Radiological Society (DRG), the process of curriculum development is described and the new curriculum is presented together with suggestions for practical implementation. MATERIALS AND METHODS: The DRG has developed a new curriculum for radiology. This was coordinated nationally among faculty via an online survey and the result was incorporated into the NKLM 2.0. Furthermore, possibilities for the practical implementation of the competency-based content are shown and different teaching concepts are presented. RESULTS: The developed curriculum is competency-based and aims to provide students with important skills and abilities for their future medical practice. The general part of the curriculum is divided into the topics "Radiation Protection", "Radiological Methods" and radiologically-relevant "Digital Skills". Furthermore, there is a special part on the individual organ systems and the specific diseases. In order to implement this in a resource-saving way, new innovative teaching concepts are needed that combine the advantages of face-to-face teaching in small groups for practical and case-based learning with digital teaching offers for resource-saving teaching of theoretical content. CONCLUSION: We have created a uniform radiology curriculum for medical studies in Germany, coordinated it nationally and integrated it into the NKLM 2.0. The curriculum forms the basis of a uniform mandatory radiology teaching and should be the basis for the individual curriculum development of each faculty and strengthen the position of radiology in the interdisciplinary context. KEY POINTS: · A radiology curriculum for undergraduate medical education was developed.. · The curriculum was brought into agreement among the faculties in Germany and integrated into the NKLM 2.0.. · This curriculum is intended to be the basis for curriculum development and to strengthen the position of radiology.. · In order to implement the competence-based teaching, new innovative teaching concepts are necessary.. CITATION FORMAT: · Dettmer S, Barkhausen J, Volmer E et al. White Paper: Radiology Curriculum for Undergraduate Medical Education in Germany and Integration into the NKLM 2.0. Fortschr Röntgenstr 2021; 193: 1294 - 1303.
EVALuna2:470229